Reading Room Lighting of Library of Bank Indonesia Surabaya - Masyhur, Madhika Kurniadi (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2024)
Lighting is one of the main factors in influencing visual comfort, especially in reading activities in facilities such as libraries. However, in practice, not all reading facilities provide good lighting, either due to lack of attention, inadvertence, aesthetic factors or because of factors that make it difficult to fulfill. One such facility is the Library of Bank Indonesia Surabaya. With the status of the library as a Cultural Heritage Building, the study of its lighting aspects will focus on spaces that require special lighting such as reading areas. The study will be conducted on the aspects of openings, furniture arrangement, and artificial lighting. In this study the method used is Descriptive-Quantitative and Experimental from the results of direct observation, Documentation, Measurement using Luxmeter and Simulation using DIALux EVO 11.1 application. With direct measurement time carried out on the same day with 3 different times, in the Morning at 09.00 - finished, Afternoon at 12.00 - finished, and Afternoon at 15.00 - finished. Then simulations are carried out to get alternatives from the variables tested to get lighting that can meet the visual comfort of users. From the results of simulations and studies carried out, it is found that changing variables such as openings, furniture arrangements and artificial lighting can provide lighting that is comfortable for the people.